2019
DOI: 10.1158/1078-0432.ccr-18-3102
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Memory CD8+ T Cells Provide Clinical Benefit in HER2 Expressing Breast Cancer: A Mouse to Human Translational Study

Abstract: Purpose: Immune-based therapy for metastatic breast cancer has had limited success, particularly in molecular subtypes with low somatic mutations rates. Strategies to augment T-cell infiltration of tumors include vaccines targeting established oncogenic drivers such as the genomic amplification of HER2. We constructed a vaccine based on a novel alphaviral vector encoding a portion of HER2 (VRP-HER2).Patients and Methods: In preclinical studies, mice were immunized with VRP-HER2 before or after implantation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 47 publications
2
58
0
Order By: Relevance
“…We recently reported on the use of CyTOF analysis to describe the changes occurring in peripheral blood immune cells after vaccination with a different VRP-based vaccine encoding the tumor antigen HER2 (VRP-HER2). 28 In that study, we also observed the expansion of an antigen-specific, cytolytic CD8 T cell population, suggesting that CyTOF may be a preferred approach for assessing immunogenicity of cancer vaccines. In the current study, CyTOF allowed us to determine that the terminally differentiated effector memory cells CD8+T EMRA were increased and Tregs were decreased in most patients following the immunizations, with the result that the CD8 T EMRA :Treg ratio increased, an important indicator of a favorable environment for antitumor immune responses.…”
Section: Discussionmentioning
confidence: 58%
“…We recently reported on the use of CyTOF analysis to describe the changes occurring in peripheral blood immune cells after vaccination with a different VRP-based vaccine encoding the tumor antigen HER2 (VRP-HER2). 28 In that study, we also observed the expansion of an antigen-specific, cytolytic CD8 T cell population, suggesting that CyTOF may be a preferred approach for assessing immunogenicity of cancer vaccines. In the current study, CyTOF allowed us to determine that the terminally differentiated effector memory cells CD8+T EMRA were increased and Tregs were decreased in most patients following the immunizations, with the result that the CD8 T EMRA :Treg ratio increased, an important indicator of a favorable environment for antitumor immune responses.…”
Section: Discussionmentioning
confidence: 58%
“…This mirrors preclinical and clinical studies with different immunotherapies in BC that demonstrate heterogeneous tumor regression associated with differences in T cell infiltration and local immunosuppression. 39 48 49 As our clinical studies suggest that the stimulation of HER2-specific memory CD8+ T cells is an important requirement for progression-free survival, 6 the use of HER2-LAMP vaccines may have a significant impact against treatment-resistant metastatic HER2+ BC. Given that effective local immunosuppression can still curtail these responses in a significant fraction of mice, HER2-LAMP vaccines may be effectively coupled with heterologous vaccines (such as our viral HER2 vectors) to further expand anti-HER2 immune responses, or with PD-1/PD-L1 immune checkpoint inhibitors to counterbalance local immunosuppression, which are the focus of our continuing investigations.…”
Section: Discussionmentioning
confidence: 99%
“…1 2 5 In our previous studies, we developed HER2-specific viral vaccines encoding inactivated and truncated forms of HER2 6 7 which we used to stimulate HER2-specific immune responses in patients with advanced HER2+ BC. 6 These studies demonstrated that viral vaccines encoding truncated forms of HER2 could break HER2specific tolerance in HER2+ BC patients, with the induction of significant HER2-specific T cell memory responses in a subset of patients. Notably, we found that these HER2-specific memory responses were associated with enhanced progression-free survival.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations